Reflectance Confocal Microscopy in the Diagnosis of Onychomycosis: A Systematic Review - Sophie Soyeon Lim; Bo Ri Kim; Je-Ho Mun (Journal of Fungi, 2022)
Accurately diagnosing onychomycosis is vital, as therapy is time-consuming and accompanied by multiple adverse effects. Reflectance confocal microscopy (RCM), in contrast to traditional mycological testing, is a noninvasive, point-of-care tool that can rapidly identify fungal lesions. This systematic review aims to understand the utility of RCM in evaluating onychomycosis and follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic search of four databases was conducted. A total of five articles—three prospective cohort studies and two case reports—which reported RCM findings in nails clinically suspicious for onychomycosis were analyzed. Fungal hyphae or spores were visualized on RCM in 67 (81.7%) of the 82 mycologically confirmed cases of onychomycosis. Terms used to describe hyphae included bright, linear, lengthy, thready-like, branching and filamentous. Spores were described as bright, roundish structures with high reflection. The three cohort studies demonstrated RCM had a sensitivity of 52.9–91.7, a specificity of 57.58–90.2%, a positive predictive value of 61.1–88.6% and a negative predictive value of 68.0–90.5%. In conclusion, existing studies demonstrate how RCM can assist the diagnosis of onychomycosis at the bedside. Larger studies incorporating multiple testing modalities to confirm the diagnosis of onychomycosis are warranted to further explore the diagnostic utility of RCM.